Patriotic Envelopes of the Civil War : The Iconography of Union and Confederate Covers - Boyd, Steven R. (Book collections on Project MUSE., 2010)
During the Civil War, private printers in both the North and South produced a vast array of envelopes featuring iconography designed to promote each side's war effort. Many of these "covers" featured depictions of soldiers, prominent political leaders, Union or Confederate flags, Miss Liberty, Martha Washington, or even runaway slaves--at least fifteen thousand pro-Union and two hundred fifty pro-Confederate designs appeared between 1861 and 1865.